Answer:
2(s-c)/ a^2 = v
Step-by-step explanation:
s = 1/2 a^2 v+c
Subtract c from each side
s -c = 1/2 a^2 v+c-c
s-c = 1/2 a^2 v
Multiply each side by 2
2(s-c) = 2* 1/2 a^2 v
2(s-c) = a^2 v
Divide each side by a^2
2(s-c)/ a^2 = a^2 v /a^2
2(s-c)/ a^2 = v
Answer:
=5x+3
Step-by-step explanation:
Answer:
The quadratic equation is x^2-2x-4
Step-by-step explanation:
We want to know the equation that has the solution below;
x = 1 ± √5
This means x = 1 + √5 or 1 - √5
The equation would thus be;
(x-1-√5)(x-1+ √5)
= x(x-1+ √5)-1(x-1+ √5)-√5(x-1+ √5)
Opening the brackets we have ;
x^2-x+ √5x-x + 1 -√5-√5x+ √5-5
collecting like terms we have;
x^2-2x+1-5
= x^2-2x-4